2020
DOI: 10.1101/2020.02.11.943464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic and Proteomic Analyses of a New Cytoplasmic Male Sterile Line with wildGossypium bickii.Genetic Background

Abstract: 39Cotton is an important fiber crop but has serious effects of heterosis, in which cytoplasmic male 40 sterility (CMS) being the major cause of heterosis in plants. However, there are no studies done on 41 CMS Yamian A in cotton with the genetic background of the Australian wild Gossypium bickii. 42 Transcriptomic and proteomic results showed that UDP-glucosyltransferase -in the nucleus, 60S 43 ribosomal protein L13a-in the cytoplasm, ribulose-1,5-bisphosphate carboxylase/oxygenase -in the 44 chloropl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…To obtain PaACLB-silenced plants, A. tumefaciens carrying pTRV2 empty vector and the previously constructed pTRV2-PaACLB1-B2 vector (Zhao, Wang, et al, 2020;Zhao, Zhong, et al, 2020) and S1), which was consistent with our previous results (Zhao, Wang, et al, 2020;Zhao, Zhong, et al, 2020).…”
Section: Paaclb1-b2 Silencing Changed the Content Of Acetyl-coa But N...supporting
confidence: 84%
See 2 more Smart Citations
“…To obtain PaACLB-silenced plants, A. tumefaciens carrying pTRV2 empty vector and the previously constructed pTRV2-PaACLB1-B2 vector (Zhao, Wang, et al, 2020;Zhao, Zhong, et al, 2020) and S1), which was consistent with our previous results (Zhao, Wang, et al, 2020;Zhao, Zhong, et al, 2020).…”
Section: Paaclb1-b2 Silencing Changed the Content Of Acetyl-coa But N...supporting
confidence: 84%
“…These results showed that crotonylation had a closer relationship with acetylation than with ubiquitination. pathway (Zhao, Wang, et al, 2020;Zhao, Zhong, et al, 2020). In the present study, proteins with different crotonylation sites were also enriched in the TCA cycle pathway.…”
Section: Close Correlation Between Lysinecrotonylated and Lysine-acet...supporting
confidence: 63%
See 1 more Smart Citation
“…Lower content of ribosomal protein during anther abortion was observed in cotton, suggesting that insufficient synthesis of ribosomal protein may have hindered pollen production [ 47 ]. However, Zhao et al [ 48 ] found that the 60S ribosomal protein L13a-4-like was up-regulated in the male sterile line and hence was related to the abortion of microspores in cotton. These results indicate that the up- or down-regulation of some key ribosomal proteins may lead to male sterility.…”
Section: Discussionmentioning
confidence: 99%
“…In cotton GMS line 2074A, GhA11G1250 encoded a mitochondrial localization of peroxisomal-like protein HSP14.5, participated in response to ROS is critical to pollen abortion (Nie et al, 2020). UDP-glucuronosyl/UDP-glucosyltransferase, 60S ribosomal protein L13a-4-like, and glutathione S-transferase, as well as heat shock protein Hsp20, ATPase, F0 complex, and subunit D were related to the microspore abortion in Yamian A, a CMS line with a wild cotton genetic background (Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%